SAKHI GA – A Step Towards Women Empowerment - Kadwadkar, Darshana Deepak (Advances in Social Sciences Research Journal, 2025)
Financial Literacy and Digital Literacy are both required in today’s era so as to plan's one’s financial security. According to the survey, in India, only 33% of women have never used the internet, and for rural women that figure drop to around 25%. Improving digital Literacy and expanding access to digital technologies is critical to tackling this digital divide and enabling women from all walks of life to benefit from digital transformation. Closing the digital gap and boosting opportunities for women to participate equally in economic life will be crucial to sustaining India's development gains and enabling a stronger and more inclusive recovery. With increasing levels of digital financial literacy it’s impact can be felt and can also become am indicator of increased economic status of women.